Anti-Inflammatory Effects of Adrenomedullin on Acute Lung Injury Induced by Carrageenan in Mice - Talero Elena; Di Paola Rosanna; Mazzon Emanuela; Emanuela Esposito; Motilva Virginia; Cuzzocrea Salvatore (Mediators of Inflammation)
Adrenomedullin (AM) is a 52 amino acid peptide that has shown predominant anti-inflammatory activities. In the present study, we evaluated the possible therapeutic effect of this peptide in an experimental model of acute inflammation, the carrageenan- (CAR-) induced pleurisy. Pleurisy was induced by injection of CAR into the pleural cavity of mice. AM (200 ng/kg) was administered by intraperitoneal route 1 h after CAR, and the animals were sacrificed 4 h after that. AM treatment attenuated the recruitment of leucocytes in the lung tissue and the generation and/or the expression of the proinflammatory cytokines as well as the expression of the intercellular cell adhesion molecules. Moreover, AM inhibited the induction of inducible nitric oxide synthase (iNOS), thereby abating the generation of nitric oxide (NO) and prevented the oxidative and nitroxidative lung tissue injury, as shown by the reduction of nitrotyrosine, malondialdehyde (MDA), and poly (ADP-ribose) polymerase (PARP) levels. Finally, we demonstrated that these anti-inflammatory effects of AM were associated with the inhibition of nuclear factor-κB (NF-κB) activation. All these parameters were markedly increased by intrapleural CAR in the absence of any treatment. We report that treatment with AM significantly reduces the development of acute lung injury by downregulating a broad spectrum of inflammatory factors.